The clinical significance of plasma neopterin in heart failure with preserved left ventricular ejection fraction. (9th November 2015) - Yamamoto, Eiichiro; Hirata, Yoshihiro; Tokitsu, Takanori; Kusaka, Hiroaki; Tabata, Noriaki; Tsujita, Kenichi; Yamamuro, Megumi; Kaikita, Koichi; Watanabe, Hiroshi; Hokimoto, Seiji; Maruyama, Toru; Ogawa, Hisao
Abstract: Aims: Although inflammation plays an important role in the pathogenesis of heart failure (HF), the precise pathophysiological role of inflammation in HF with preserved left ventricular ejection fraction (HFpEF) still remains unclear. Hence, we examined the clinical significance of plasma neopterin, an inflammatory biomarker, in HFpEF patients. Methods and results: In the present study, we recruited consecutive HFpEF patients hospitalized in Kumamoto University Hospital, and further measured plasma neopterin by high‐performance liquid chromatography and serum derivatives of reactive oxidative metabolites (DROM), a new biomarker of reactive oxygen species. Compared with risk factors (number of patients, age, sex, and equal incidence of diabetes mellitus, hypertension, and dyslipidemia) ‐matched non‐HF patients ( n  = 68), plasma neopterin levels, but not serum high‐sensitivity C‐reactive protein levels, were significantly increased in patients with HFpEF ( n  = 68) ( P  < 0.001 and P  = 0.15, respectively), accompanied by an elevation in serum DROM levels ( P  < 0.001). Plasma neopterin levels in New York Heart Association (NYHA) class III/IV HFpEF patients were significantly higher than in NYHA class II patients ( P  < 0.004). Furthermore, plasma ln‐neopterin levels had significant and positive correlation with ln‐DROM values ( r  = 0.57) and parameters of cardiac diastolic dysfunction [the ratio of early transmitral flow velocity to tissue Doppler early diastolic mitral annular velocity ( r  = 0.34), left atrial volume index ( r  = 0.17), and B‐type natriuretic peptide ( r  = 0.38)]. Kaplan–Meier analysis showed that the high‐neopterin group (>51.5 nM: median value of neopterin in HFpEF patients) had a higher probability of cardiovascular events than the low‐neopterin group (log‐rank test, P  = 0.003). Conclusions: Plasma neopterin levels significantly increased in HFpEF and correlated with the severity of HF. Furthermore, high neopterin were significantly correlated with future cardiovascular events, indicating that measurement of plasma neopterin might provide clinical benefits for risk stratification of HFpEF patients. © 2015 The Authors. ESC Heart Failure published by John Wiley & Sons Ltd on behalf of the European Society of Cardiology.